Pengembangan Evaluasi Pembelajaran Berbasis HOTS Pada Mata Kuliah Instalasi Perumahan - Irna Mariati; Oriza Candra (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
This study uses the research and development method of R&D (Research & Development) with a 4D model consisting of 4 stages, namely define, design, develop and disseminate. The subjects of this study were students of Electrical Engineering, Faculty of Engineering, Padang State University who had completed the housing installation course. This research was conducted because currently there are still many educators who make test instruments that only measure the low-level abilities of students such as C1 and C2, so the researchers aim to produce a HOTS-based test instrument that is useful for learning evaluation. The data in this study used a validation sheet given to two validators. Based on the results of the study, the validity data was obtained from two validators, namely validator 1 of 81.8% and validator 2 of 88.6%. based on the results obtained from the two validators is 85% with a valid category and the reliability results are declared reliable with a value of 0.70%. Practical test conducted by lecturers majoring in electrical engineering and 30 electrical engineering students who have completed the housing installation course. The results of the practicality questionnaire filled out by the lecturers were stated to be very practical and the results from the respondents were very practical with a percentage value of. it was concluded that the test instrument was valid, reliable, and practical to use as an evaluation of housing installation learning.